Agronomic characterization of third cycle strawberry plants grown in substrate - Baldin, Katia Birgeier; Negrelli, Welton Schiles; Lima , Cláudia Simone Madruga; Leandrini , Josimeire Aparecida; Oliveira , Rivael de Jesus; Rufato, Leo (Revista de Ciências Agroveterinárias, 2023)
Strawberry (Fragaria x ananassa Duchesne) is the main small fruit produced in Brazil. This can be cultivated in soil and/or substrate cultivation systems, which allows this plant to be used for more than one production cycle. Thus, the present work aims to evaluate the agronomic behavior of third-cycle strawberry plants grown in organically managed substrate. The cultivars used were Randoce (short day) and Bella (neutral day). The containers used were vases and slabs. The experimental design was completely randomized in a factorial scheme. The evaluations carried out were: number of leaves and crowns, crown diameter, total chlorophyll content, dates of flowering and harvest, number of fruits, diameter and length of fruits, soluble solids content, fresh mass and total production. Data were compared using Tukey’s test. The neutral-day cultivar, regardless of the cultivation system, started flowering earlier than the short-day cultivar. The productive results were lower than expected for the crop. The temperature, the low accumulation of plant reserves and the consequent appearance of pests and diseases may have influenced the lower performance of the third cycle plant. It is concluded that third cycle strawberry plants, regardless of cultivar and cultivation container, present lower agronomic performance in relation to the previous two years of cultivation.